Ruthenium Nanoparticles Supported on Carbon Microfibers for Hydrogen Evolution Electrocatalysis. Issue 15 (23rd January 2019) - Creus, Jordi; Mallón, Laura; Romero, Nuria; Bofill, Roger; Moya, Alicia; Fierro, Jose L. G.; Mas‐Ballesté, Rubén; Sala, Xavier; Philippot, Karine; García‐Antón, Jordi
Abstract : Four different cathodes for the hydrogen evolution reaction (HER) have been developed by the decoration of commercial carbon microfibers with Ru nanoparticles (Ru NPs). Two types of carbon fibers have been used: pristine, as‐received, carbon fibers (pCF) and carbon fibers modified by an oxidative treatment that led to the functionalization of their surface with carboxylic groups (fCF). The decoration of these CFs with Ru NPs has been performed by two different methodologies based on the organometallic approach: direct synthesis of Ru NPs on top of the CFs ( in‐situ Ru NPs) or impregnation of the CFs with a colloidal solution of preformed Ru NPs stabilized with 4‐phenylpyridine (RuPP NPs; ex‐situ Ru NPs). The electrocatalytic performance of these four cathodes ( ex‐situ RuPP@pCF and RuPP@fCF; in‐situ Ru@pCF and Ru@fCF) for the HER has been studied in acidic conditions. The results obtained show that both the nature of the NPs and of the carbon fibers play a key role on the stability and activity of the hybrid electrodes: ex‐situ prepared Ru NPs afford better activities at lower overpotentials and better stabilities than those formed in‐situ . Among the two ex‐situ systems, an enhancement of the stability with pCF is observed, that may arise from more effective π‐interactions between 4‐phenylpyridine ligand and the surface of these carbon fibers. This interaction is somehow disfavored with fCF due to the presence of the surface carboxylic groups. Abstract : Four heterogeneous hybrid cathodes for the catalytic hydrogen evolution reaction (HER) have been prepared combining two types of carbon fibers and two different synthetic methodologies in order to decorate their surface with Ru nanoparticles. The activity and stability of all the hybrid systems have been evaluated.